PENDAMPINGAN KELOMPOK USAHA PENCACAHAN LIMBAH PLASTIK DI KABUPATEN MALANG - Wijayanto, Adi; Rusdi, Rusdi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2017)
Plastic bottles have become part of the daily activities, especially in activities relating to packaging of mineral water. The use of plastic bottles for packaging of mineral water is an alternative that is practical and concise, but on the other hand is also harmful to the environment because it adds to discharge garbage plastic bottles. Plastic bottles is not derived from biological compounds, plastic bottles have difficult nature degraded (non - biodegradable) that can contaminate soil, water, sea, and even air. Specific target science and technology community service programs for the community (IBM) are (1) understanding of the technological waste processing machine plastic bottles into plastic pellets, (2) the public's understanding of the plastic bottle waste management, (3) labor absorption and production of plastic pellets more leverage. The program will increase the sale value of plastic garbage that has become plastic pellets, so as to improve the economic welfare of society. Activities in this program include: (1) design and design thrasher plastic pellets, (2) sending power to the transfer of knowledge (apprentice), (3) socialization to the community group enumerator plastic pellets, (4) submission thrasher plastic pellets, (5) trial thrasher plastic pellets, (6) the application of machines in the field and practice of making plastic pellets, (7) management training.